2022
DOI: 10.1182/bloodadvances.2021006470
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet medications and risk of intracranial hemorrhage in patients with metastatic brain tumors

Abstract: Although intracranial hemorrhage (ICH) is frequent in the setting of brain metastases, there are limited data on the influence of antiplatelet agents on the development of brain-tumor associated ICH. To evaluate whether the administration of anti-platelet agents increases the risk of ICH, we performed a matched cohort analysis of patients with metastatic brain tumors with blinded radiology review. Study population included 392 patients with metastatic brain tumors (134 received antiplatelet agents and 258 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…A recent meta-analysis reported that anticoagulation resulted in an increased risk of intracerebral haemorrhage by more than 3-fold in patients with gliomas but had no effect on brain metastasis 15 . For primary brain tumours 16 and metastatic brain tumours 17 , antiplatelet also induced no increase in the incidence of intracerebral haemorrhage. Therefore, to exclude this confounding effect, we excluded patients from our cohort if antiplatelet or anticoagulant were medicated.…”
Section: Discussionmentioning
confidence: 88%
“…A recent meta-analysis reported that anticoagulation resulted in an increased risk of intracerebral haemorrhage by more than 3-fold in patients with gliomas but had no effect on brain metastasis 15 . For primary brain tumours 16 and metastatic brain tumours 17 , antiplatelet also induced no increase in the incidence of intracerebral haemorrhage. Therefore, to exclude this confounding effect, we excluded patients from our cohort if antiplatelet or anticoagulant were medicated.…”
Section: Discussionmentioning
confidence: 88%
“…Nonetheless, some of these trials that were designed to evaluate these chemo-preventive effects of selective COX-2 inhibitors, such as celecoxib and rofecoxib, showed an increased risk of major adverse cardiovascular events and were halted [94,95]. On contrast to selective COX-2 inhibitors, RCTs, observational case-control and meta-analysis studies have demonstrated a chemo-preventive effect of aspirin against colorectal cancers [96][97][98][99][100][101]. Other studies have also demonstrated that aspirin reduced the risk of death from several noncolonic solid cancers including esophageal, pancreatic, brain, lung, stomach, and prostate cancer in patients with Lynch syndrome [101,102].…”
Section: Aspirinmentioning
confidence: 99%